A Multimetric Evaluation of Online Patient Educational Materials for Breast Implant–associated Anaplastic Large Cell Lymphoma. Issue 5 (10th August 2021) - Miles, Randy C; Lourenco, Ana P; Baird, Grayson L; Roy, Ishita T; Choi, Paul H S; Lehman, Constance; Lamb, Leslie R
Abstract: Objective: To assess understandability, actionability, and readability of online patient educational materials (OPEM) related to breast implant–associated anaplastic large cell lymphoma (BIA-ALCL). Methods: Search volumes for query terms related to BIA-ALCL including "breast implant associated lymphoma, " "breast implant associated anaplastic large cell lymphoma, " and "BIA-ALCL" were analyzed in one-week increments and normalized to total Google search volume. The same terms were then queried using an online search engine to identify commonly accessed OPEM on this topic. Understandability and actionability of OPEM were evaluated using the Patient Education Materials Assessment Tool. Grade-level readability was determined using generalized estimating equations, with observations nested within readability metrics from each website. All interval estimates were calculated for 95% confidence. Results: Overall, 24 websites were identified based on search parameters. Of these websites, 11 (45.8%) met criteria for understandability, and 1 (4.2%) met criteria for actionability. Overall, readability ranged from 10.2 to 17.3 for all websites with an average grade level readability of 12.4; 0 websites were written at or below a sixth-grade reading level. Government websites had the highest average grade reading level at 14.0, followed by commercial websites at 13.2, nonprofit websites at 12.0, and then academic/hospital-based websites at 11.5. Conclusion: The quality of available OPEM on BIA-ALCL is limited. Future development of OPEM should be designed with the goal of improving both comprehension and actionability to help reduce patient anxiety and unnecessary clinical appointments related to this disease.